2021
DOI: 10.1155/2021/6124346
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrasonic Image Restoration Algorithm for Prevention of Nervous Disorders during the Recovery Period of Patients Receiving Sevoflurane Anesthesia

Abstract: In this article, dexmedetomidine (Dex) was used to prevent neurological disorders in patients anesthetized with sevoflurane and the effect was analyzed using ultrasound images based on the restoration algorithm of the linear system model. Children injected with Dex were in the experimental group, while children injected with normal saline were in the control group. The mean arterial pressure (MAP), arterial oxygen saturation (SpO2), heart rate (HR), Pediatric anesthesia agitation scale (PAED) score, Face, Legs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%